2013
DOI: 10.1007/s00343-013-2072-8
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability in the North Pacific meridional overturning circulation

Abstract: We analyzed the temporal and spatial variation, and interannual variability of the North Pacifi c meridional overturning circulation using an empirical orthogonal function method, and calculated mass transport using Simple Ocean Data Assimilation Data from 1958-2008. The meridional streamfunction fi eld in the North Pacifi c tilts N-S; the Tropical Cell (TC), Subtropical Cell (STC), and Deep Tropical Cell (DTC) may be in phase on an annual time scale; the TC and the STC are out of phase on an interannual time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Wu and Liu (2003) suggested that the regional SST variations in central and eastern North Pacific are separately resulted from changes of Ekman advection and surface heat flux, both of which are affected by the subtropical ocean circulation, as a part of meridional overturning circulation in North Pacific (NPMOC). The NPMOC has been found to work as a bridge for mass and heat exchanges (McCreary and Yu, 1992;Liu et al, 1994), and is largely driven by sea surface wind stress and resulting in east-west sea level slope Liu et al, 2013). However, there are larger discrepancies in the estimates of drag coefficients among different computational approaches, especially due to uncertainties in velocity measurements and removal of non-wind-driven currents.…”
mentioning
confidence: 99%
“…Wu and Liu (2003) suggested that the regional SST variations in central and eastern North Pacific are separately resulted from changes of Ekman advection and surface heat flux, both of which are affected by the subtropical ocean circulation, as a part of meridional overturning circulation in North Pacific (NPMOC). The NPMOC has been found to work as a bridge for mass and heat exchanges (McCreary and Yu, 1992;Liu et al, 1994), and is largely driven by sea surface wind stress and resulting in east-west sea level slope Liu et al, 2013). However, there are larger discrepancies in the estimates of drag coefficients among different computational approaches, especially due to uncertainties in velocity measurements and removal of non-wind-driven currents.…”
mentioning
confidence: 99%